Effectiveness of N-Acetylcysteine in the Treatment of Renal Deterioration Caused by Long-Term Exposure to Bisphenol A - Anongporn Kobroob; Wachirasek Peerapanyasut; Sirinart Kumfu; Nipon Chattipakorn; Orawan Wongmekiat (Biomolecules, 2021)
Human health hazards caused by bisphenol A (BPA), a precursor for epoxy resins and polycarbonate-based plastics, are well documented and are closely associated with mitochondrial impairment and oxidative imbalance. This study aimed to assess the therapeutic efficacy of N-acetylcysteine (NAC) on renal deterioration caused by long-term BPA exposure and examine the signaling transduction pathway involved. Male Wistar rats were given vehicle or BPA orally for 12 weeks then the BPA-treated group was subdivided to receive vehicle or NAC concurrently with BPA for a further 4 weeks, while the vehicle-treated normal control group continued to receive vehicle through to the end of experiment. Proteinuria, azotemia, glomerular filtration reduction and histopathological abnormalities caused by chronic BPA exposure were significantly reduced following NAC therapy. NAC also diminished nitric oxide and lipid peroxidation but enhanced renal glutathione levels, and counteracted BPA-induced mitochondrial swelling, increased mitochondrial reactive oxygen species production, and the loss of mitochondrial membrane potential. The benefit of NAC was related to the modulation of signaling proteins in the AMPK-SIRT3-SOD2 axis. The present study shows the potential of NAC to restore mitochondrial integrity and oxidative balance after long-term BPA exposure, and suggests that NAC therapy is an effective approach to tackle renal deterioration in this condition.